Digital citizenship: definition and construction of a national activity-based index - Linares-Torres, Freddy (2023)
Digital activity impacts multiple aspects of contemporary society, including the economy, government and education. Moreover, given the complexity of online activities and the development of the digital society, Digital Citizenship should be seen as a scale encompassing various levels of digital participation and skills. Therefore, appropriate methods are required to assess and optimally monitor this dimension based on people's online activity. The article focuses on the definition and construction of a Digital Activity Index (InAD) in Peru with the aim of identifying patterns in internet access (incidence) and use (intensity) that represent opportunities for improving the digital profile in Peru. The study uses the Alkire-Foster methodology to create the InAD Peru based on data from the National Household Survey (ENAHO) from 2015 to 2023. The results of InAD Peru show a steady increase in digital activity. However, this is mainly explained by increased connectivity and highlights that not all digital activities are performed in the same proportion. Results are also provided by region, allowing for the identification of areas with specific needs. In conclusion, measuring and understanding digital citizenship in Peru through a more comprehensive approach, such as with the InAD, is relevant. It is hoped that the InAD can help promote a stronger digital profile in Peruvian society and potentially serve as a model for other countries.